Turbulence, Firm Decentralization and Growth in Bad Times - Philippe Aghion; Nicholas Bloom; Brian Lucking; Raffaella Sadun; John Van Reenen (Institute of Labor Economics (IZA), 2017)
What is the optimal form of firm organization during "bad times"? Using two large micro datasets on firm decentralization from US administrative data and 10 OECD countries, we find that firms that delegated more power from the Central Headquarters to local plant managers prior to the Great Recession out-performed their centralized counterparts in sectors that were hardest hit by the subsequent crisis. We present a model where higher turbulence benefits decentralized firms because the value of local information and urgent action increases. Since turbulence rises in severe downturns, decentralized firms do relatively better. We show that the data support our model over alternative explanations such as recession-induced reduction in agency costs (due to managerial fears of bankruptcy) and changing coordination costs. Countries with more decentralized firms (like the US) weathered the 2008 09 Great Recession better: these organizational differences could account for about 16% of international differences in post-crisis GDP growth.
Keywords: O31; O32; O33; F23; 330; decentralization; growth; turbulence; Great Recession